PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR METEMATIKASISWA KELAS VIIISMPN 11 PINGGIR - Zetri, Wenny; Yuanita, Putri; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to improve the learning process and learning outcomes math class VIII SMPN 11 Pinggir by applying Cooperative learning model Students Teams Achievement Division (STAD) type. The subjects were students of class VIII A with heterogen academic ability. This research is a class action with two cycles. Each cycle has four steps, the steps are the planning, implementation, observation and reflection. Results showed activity sheets and teacher observation of students have done well after taking action. There is an improvement in thestudents learning process and an increase in the number of students who achieved at UH minimum completeness criteria end of each cycle compared to the number of students who achieve minimum completeness criteria on base score. The results of this study indicate that the application of cooperative learning model Students Teams Achievement Division (STAD) can improve the process of learning and improving mathematics learning outcomes of VII A Student in the SMPN 11 Pinggir on first semester of academic year 2013/2014.Keywords: Mathematics Learning Outcomes, Cooperative Learning, Students Teams Achievement Division (STAD), Classroom Action Research